Alzheimer's disease susceptibility genes modify the risk of Parkinson disease and Parkinson's disease-associated cognitive impairment. (11th June 2018) - Fang, Lu; Tang, Bei-sha; Fan, Kuan; Wan, Chang-min; Yan, Xin-xiang; Guo, Ji-feng
Highlights: Systematically analyzed the monogenic and polygenic relationship between 16 CE-related SNPs and the risk of PD and PD-CI. The first report to use gene–gene interactions in the association between AD-related genes and PD or PD-D. The APOE ε4 allele is associated with a higher risk for PD-D. Gene-gene interaction analysis suggests that PD/PD-D and AD may share convergent pathways through gene–gene interactions. Abstract: The pathogenic mechanism underlying Parkinson's disease (PD) and PD- Cognitive impairment (CI) remains elusive. Its potential link to the risk factors in Alzheimer's disease (AD) is unclear. In this study, we analyzed 16 CE-associated single nucleotide polymorphisms (SNPs) in twelve genes in a Chinese cohort of 450 PD cases and 449 controls. Among our 298 cases clinically evaluated for CI, 113 cases did not show CI signs (PD-NC), 86 cases had mildly cognitive impairment (PD-MCI) and 99 cases had dementia (PD-D). We found that the APOE ε4 allele is associated with a higher risk for PD-D. Gene-gene interaction analysis revealed that three significant gene–gene interactions, including BDNF and CLU, APOE and CR1, and DYRK1A and CD2AP increase the risk for PD. Because these SNPs are known genetic risk factors for AD, their contribution to PD and PD-D shown in this study suggests that PD/PD-D and AD may share convergent pathways in their pathogenesis through gene–gene interactions.